2006
DOI: 10.7863/jum.2006.25.7.837
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Idiopathic Hydrocele Has a Substantial Effect on the Ipsilateral Testicular Geometry and Resistivity Indices

Abstract: Unilateral idiopathic hydrocele has a tendency for rounding rather than flattening the ipsilateral testis as well as elevating the RI(sc) on the affected side. To the best of our knowledge, no strict spectral Doppler analysis criteria have been proposed for testicular ischemia yet. Therefore, the impact of the difference of the RI(sc) should raise the suspicion for ischemia, and further research is needed to elucidate any effect on spermatogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…This result seems to agree with the explanatory mechanism we proposed, which concerned the possible impairment of the venous drainage by the pressure effect of the hernia sac in the inguinal region. It is evident that this relevant finding is in accordance with findings from our previous study 15 as well as those reported by Beddy et al 1 and Mihmanli et al 14 Unfortunately, in this study, we did not attempt to assess the venous blood flow from the testes during the ultrasonographic examinations, which would help us clarify the mechanism associated with our findings. On the other hand, an interesting finding in our study was that the relevant spectral Doppler indices in the subcapsular arteries were found to be decreased in the ipsilateral testes compared with the contralateral testes, although it seems to contradict the mechanism for vascular impairment proposed by the aforementioned studies on the topic.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result seems to agree with the explanatory mechanism we proposed, which concerned the possible impairment of the venous drainage by the pressure effect of the hernia sac in the inguinal region. It is evident that this relevant finding is in accordance with findings from our previous study 15 as well as those reported by Beddy et al 1 and Mihmanli et al 14 Unfortunately, in this study, we did not attempt to assess the venous blood flow from the testes during the ultrasonographic examinations, which would help us clarify the mechanism associated with our findings. On the other hand, an interesting finding in our study was that the relevant spectral Doppler indices in the subcapsular arteries were found to be decreased in the ipsilateral testes compared with the contralateral testes, although it seems to contradict the mechanism for vascular impairment proposed by the aforementioned studies on the topic.…”
Section: Discussionsupporting
confidence: 93%
“…1 Conflicting reports have been presented in the literature regarding the effect of a hydrocele, which may be detected with an inguinal hernia as well, on V t , although it has been assumed to have an increased pressure effect on the testicular vasculature. 11,14,15 In a recent study by Biagiotti et al, 12 a significant correlation was detected between the testicular RI and peak systolic velocity and spermatogenesis, and the use of those parameters was suggested as an alternative method for bloodless testing of sperm counts in infertile men. Importantly, increased testicular RI values at different levels have been reported in several studies on groups of patients with hydroceles and varicoceles in which an associated decrease of testicular function may be expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemorrhage or hematoma may be particularly likely to cause TCS if the patient is taking anticoagulant medication. Hydrocele can cause TCS by altering the shape of the testicle through compression and increasing the pulsatility and resistive indices (27,28). Mihmanli et al .…”
Section: Etiologymentioning
confidence: 99%
“…The testis, furthermore, looks compressed from the fluid collection and Doppler interrogation shows avascular testis, high-resistance flows, or diastolic flow reversal. 32,33 The course of the spermatic cord is normal. In the setting of acute scrotal pain and a large hydrocele, tension hydrocele should be considered to prevent unnecessary surgery.…”
Section: Tension Hydrocelementioning
confidence: 99%